The ironing man - Campbell, Colin (Cambridge English readers. Level 3, 1999)
While Tom is at work in London, his wife Marina is left bored and alone in the small village where they live. She wishes for someone to do the housework for her and a strange thing happens. Her wish comes true; the Ironing Man enters her life, and everything begins to change for both Marina and Tom.